Investigating Rice Blast Resistance Gene Distribution among Landrace Rice Varieties in Lower Northern Thailand for Improving Rice Cultivars - Sittichai Urtgam; Kawee Sujipuli; Urasri Suyasunanont; Nontaporn Rattanachak; Jirapas Jongjitwimol; Touchkanin Jongjitvimol (International Journal of Agronomy)
Rice blast disease caused by the fungus Pyricularia oryzae is considered as one of the severe diseases, leading to reduce tremendous rice productivity in its cultivated areas of Thailand. Due to the rapid evolution and high genetic diversity of the pathogen, the innate rice resistance (R) genes associated with defense mechanisms are significantly considered as the most important for rice breeding program to create new rice varieties, resistant to blast disease. This study aimed to investigate the rice blast R genes (Pi9, Pib, and Pi-ta) in 98 landrace rice germplasms collected from three different provinces in lower northern Thailand, Phichit (PCT), Phitsanulok (PLK), and Sukhothai (STI) through PCR assay. The results showed that the Pi-ta gene was presented in 29 different varieties, making it the most widespread, whereas the Pi9 and Pib genes were found in 28 and 25 varieties, respectively. The distribution percentage of studied genes in PLK and STI germplasms is higher than in PCT germplasms. Interestingly, only eight landrace rice varieties (varieties no. 46, 47, 48, 51, 66, 76, 81, and 90) collected from PLK and STI germplasms contain all of these three resistance genes. This finding provided the genetic information and diversity of the R genes across landrace rice varieties in the lower north of Thailand. Moreover, these R genes could be useful as genetic resources for rice improvement with resistance to blast disease through breeding program in the future.